Economic values of Begait cattle breeding-objective traits under low and medium input production systems in northern Ethiopia - Mezgebe, Gebretnsae; Gizaw, Solomon; Urge, Mengistu (2018)
The study was conducted to estimate the economic values (EV) of Begait cattle breeding-objective traits and their effects on the returns to investment in breeding programs using bio-economic model. Production systems were described according to their level of input and sale age, namely, low input herd management (LIHM) and medium input herd management (MIHM) based on fixed herd size for genetic improvement of multiple traits. Results showed that all considered traits have positive economic values across production systems except pre weaning daily body weight gain (PrDG). However, production systems had significant influence on the magnitude of EV of traits. The MIHM was superior by 100 to 9% to the LIHM system. Regardless of the two production systems, calving interval (CI) had the highest EV followed by dressing percentage (DP) and mature weight (MWT). Although, the overall change of beef trait EV influenced the marginal profit through price and production variable changes at constant MY, the more sensitive change was observed with the changes of MY EV. Traits of milk yield had 1 to 12% increment on profit with 1 to10% improvement in its EV by rising milk price, reduced weaning and reduced culling rates. However, beef traits only made 5.1×10-7 to 2.3×10 -6% raises on profits with 18 to 50% increment in its EV by beef price increment and reduced age at first calving. The higher increments of profit parallel to the EV of milk production trait and mostly simultaneous improvements on CI have a great indication to give priorities on milk yield traits than beef traits in any Begait cattle improvement program. Therefore, improving milk production traits and fecundity traits simultaneously with their market outlet is better to increase the profitability of farmers and sustains the valuable breed in their habitat.